Organic carbon stored in soils under different land uses and soil textures in southeast Argentinean Mesopotamia - Lupi, Ana Maria (2021)
Soil use affects soil organic carbon (OC) stocks by regulating the quantity and quality of incorporated organic matter. Understanding how soil texture and other factors control OC concentration and accumulation would be useful for designing sustainable soil management practices in order to promote and preserve OC storage. The aim of this work was to evaluate the effects of land use and soil texture on the vertical distribution and stock of OC in soils of the Argentinean Mesopotamia. In Entre Ríos Province, Argentina, the following sites were selected: native forest in a Typic Halacuept soil (fine to medium texture), agriculture and Eucalyptus grandis plantations of different ages (2–4 and 8–10 years) in Argic Peluderts soils (fine textures) and E. grandis plantations of different ages (2–4 and 8–10 years) in Oxic Udifluvents soils (coarse textures). OC concentration and stock were quantified up to 1 m depth, analysing distribution across the depth of the soil profile. The major differences in OC stock in equivalent mass were associated with texture; the average for coarse Oxic Udifluvents soils was 57.2 Mg OC ha− 1 and 162.3 Mg OC ha− 1 for Typic Halacuept and Argic Peluderts (fine to medium textures). Forest sites with fine textures stored three times more OC in equivalent mass than coarse textures under similar land use. No significant differences were observed between OC stock in equivalent mass in agricultural versus Eucalyptus plantations of similar texture. Sites with 8–10-year-old forest plantations in coarse soils were a special case, as they presented a great proportion of OC (60%) under 40 cm depth, due to a strong textural gradient with depth.